Elevated human chorionic gonadotrophin levels in a patient with pancreatic carcinoma presenting with a testicular metastasis. Issue 782 (December 1990) - Taylor, H.; Heaton, N.; Farrands, P.; Kirkham, N.; Fletcher, M.
Abstract : Elevated levels of human chorionic gonadotrophin are associated with primary testicular tumours and usually indicate the presence of trophoblastic elements. Human chorionic gonadotrophin can also be secreted by extragonadal tumours which may metastasize to the testes. A patient is described presenting with a testicular tumour secreting human chorionic gonadotrophin which later proved to be a metastasis from a pancreatic adenocarcinoma. Up to 70% of malignant pancreatic tumours can secrete human chorionic gonadotrophin.